Could the integration and development of teachers' pastoral role into the childcare framework provide a key to rebalancing child protection work so as to prioritise Section 17 and Part III of the Children Act 1989? - Wild, Charles Richard (2001)
The hypothesis underpinning this research study suggests that the integration of schools into the childcare framework could provide a key to re-balancing child protection work so as to prioritise the Children Act's family support provisions. It is the researcher's contention that an essential element in this re-balancing process would be the development of a more effective early detection system. In this respect, it is proposed that the educational establishment could fulfil this role given its unique position to gather information and to liaise with other agencies at a community level. Whilst this position has been recognised to a limited extent, the education service could be utilised to a far greater extent to reinforce the philosophy of the 'Framework for the Assessment of Children in Need and their Families' and as such Part III of the Children Act. A brief summary of the implications and considerations to arise from an analysis of the research data is as follows: Information concerning children in need is available within schools, though the utilisation of this information varied considerably between schools. Liaison can successfully take place between schools and other agencies at a community level. Greater clarification is required in terms of the scope a Child Protection Liaison Teacher's duties/responsibilities in order to address the variation in practice indicated by the sample. Consequently, formalisation in terms of guidance documentation, training and/or the personnel undertaking the role of CPLT is required. Greater support and training of teaching staff in general is also required if schools are to be integrated into the childcare framework. Whilst schools could undertake the early detection role proposed by the hypothesis a great deal will nevertheless depend upon how that information is subsequently utilised, (i. e. in order to identify children in need or to pursue the current practice of risk assessment